Role of Esrrg in the fibrate-mediated regulation of lipid metabolism genes in human ApoA-I transgenic mice - Sanoudou, D.; Duka, A.; Drosatos, K.; Hayes, K. C.; Zannis, V. I. (Pharmacogenomics JPharmacogenomics JPharmacogenomics J, 2010)
We have used a new ApoA-I transgenic mouse model to identify by global gene expression profiling, candidate genes that affect lipid and lipoprotein metabolism in response to fenofibrate treatment. Multilevel bioinformatical analysis and stringent selection criteria (2-fold change, 0% false discovery rate) identified 267 significantly changed genes involved in several molecular pathways. The fenofibrate-treated group did not have significantly altered levels of hepatic human APOA-I mRNA and plasma ApoA-I compared with the control group. However, the treatment increased cholesterol levels to 1.95-fold mainly due to the increase in high-density lipoprotein (HDL) cholesterol. The observed changes in HDL are associated with the upregulation of genes involved in phospholipid biosynthesis and lipid hydrolysis, as well as phospholipid transfer protein. Significant upregulation was observed in genes involved in fatty acid transport and beta-oxidation, but not in those of fatty acid and cholesterol biosynthesis, Krebs cycle and gluconeogenesis. Fenofibrate changed significantly the expression of seven transcription factors. The estrogen receptor-related gamma gene was upregulated 2.36-fold and had a significant positive correlation with genes of lipid and lipoprotein metabolism and mitochondrial functions, indicating an important role of this orphan receptor in mediating the fenofibrate-induced activation of a specific subset of its target genes.
Keywords: Animals; Apolipoprotein A-I/*genetics; Cholesterol, HDL/blood; Female; Fenofibrate/pharmacology/*therapeutic use; gene expression profiling; Gene Expression Regulation/drug effects; Humans; Lipid Metabolism/*genetics; Metabolic Networks and Pathways/drug effects/genetics; Mice; Mice, Transgenic; Protein Array Analysis; Receptors, Estrogen/*genetics; RNA, Messenger/metabolism; Transcription Factors/genetics; Up-Regulation